1963
DOI: 10.1172/jci104878
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study of Human Rectal Epithelial Cells. I. Atypical Zone of H3 Thymidine Incorporation in Mucosa of Multiple Polyposis

Abstract: The use of labeled precursors that incorporate within the cells of the gastrointestinal tract has made it possible to study cell migration, the life span of cells, and other parameters describing the DNA, RNA, and protein metabolism of these cells. Numerous isotopic investigations related to cell function in the gastrointestinal tract have been carried out in animals (1, 2), but relatively few have been performed in human subjects (3)(4)(5). Isotopic studies with precursors such as H3 thymidine, which is incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

1969
1969
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(28 citation statements)
references
References 13 publications
4
24
0
Order By: Relevance
“…3 H]thymidine labeling of colonic crypts, [17][18][19][20] whereby shifts in the labeling indices (for S phase cells) were also discovered in FAP and adenomatous crypts. This upward-shifting of transitions between crypt cell phenotypes-from stem (survivin-negative/ABK inactive) to proliferating (survivin-positive/ABK active) to terminally differentiated (survivin-negative/ABK inactive) to apoptotic cells-indicates that survivin signaling becomes dysregulated in a way that delays maturation of cells migrating up the crypt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 H]thymidine labeling of colonic crypts, [17][18][19][20] whereby shifts in the labeling indices (for S phase cells) were also discovered in FAP and adenomatous crypts. This upward-shifting of transitions between crypt cell phenotypes-from stem (survivin-negative/ABK inactive) to proliferating (survivin-positive/ABK active) to terminally differentiated (survivin-negative/ABK inactive) to apoptotic cells-indicates that survivin signaling becomes dysregulated in a way that delays maturation of cells migrating up the crypt.…”
Section: Discussionmentioning
confidence: 99%
“…In colonic crypts of FAP patients, individuals who have a CRC-initiating, germline APC mutation, the population of proliferating cells is shifted toward the crypt top (as indicated by the labeling index), [17][18][19][20] which indicates that maturation of cells is delayed as cells migrate up the premalignant crypt axis. Our study of FAP crypts 2 and Apc Min/ϩ mouse crypts 3 indicated that mutation of APC allows survivin to be overexpressed and proliferative cell populations to expand, thereby contributing to initiation of tumorigenesis.…”
mentioning
confidence: 99%
“…In our initial efforts to maintain mucosal biopsies from the small intestine in vitro, we used methods similar to those applied previously, with some success, to the in vitro culture of human rectal mucosa (21)(22)(23). These methods actually resembled tissue culture techniques in which biopsies were immersed in tissue culture medium such as Eagle's basic salt solution and were then oxygenated by agitation in a metabolic shaker after they were gassed with 95% 02 and 5% C02.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with recent immunostaining studies in human colonic crypts for Musashi-1 protein, a putative SC marker, indicating that there are, on average, 19 SCs per crypt (14). Uptake of [ 3 H]thymidine or BrdUrd by cells in human colonic crypts enables in vivo pulse-labeling of DNA-synthesizing S-phase cells (15)(16)(17)(18); when plotted, this yields the LI Normal ( Fig. 2A).…”
Section: Methodsmentioning
confidence: 99%